Prophylactic plasma transfusion for patients undergoing non-cardiac surgery - Huber, J; Stanworth, SJ; Doree, C; Trivella, M-H; Brunskill, SJ; Hopewell, SL; Wilkinson, KL; Estcourt, L (Wiley, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To determine the clinical effectiveness and safety of prophylactic plasma transfusion for peoplewith confirmed or presumed coagulopathy requiring non-cardiac surgery.